1996
DOI: 10.1002/art.1780391210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sulfasalazine and placebo in the treatment of psoriatic arthritis. A department of veterans affairs cooperative study

Abstract: Objective. To determine whether sulfasalazine (SSZ) at a dosage of 2,000 mg/day is effective for the treatment of active psoriatic arthritis (PsA) resistant to nonsteroidal antiinflammatory drug therapy.Methods. Two hundred twenty-one patients with PsA were recruited from 15 clinics, randomized (doubleblind) to SSZ or placebo treatment, and followed up for 36 weeks. Treatment response was based on joint p a i d Address reprint request requests to Daniel 0. Clegg, MD, Division of Rheumatology, 4B200-SOM, 50 Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
207
1
25

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(240 citation statements)
references
References 11 publications
(13 reference statements)
2
207
1
25
Order By: Relevance
“…In this multicenter, randomized, doubleblind, placebo-controlled trial, 405 patients were randomized in a blinded manner (1:1.3:1.3) by a centralized interactive voice response system (ClinPhone, Princeton, NJ) to receive subcutaneous injections of placebo, golimumab 50 mg, or golimumab 100 mg at weeks 0, 4,8,12,16, and 20. Randomization was stratified by baseline MTX use (yes/no).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this multicenter, randomized, doubleblind, placebo-controlled trial, 405 patients were randomized in a blinded manner (1:1.3:1.3) by a centralized interactive voice response system (ClinPhone, Princeton, NJ) to receive subcutaneous injections of placebo, golimumab 50 mg, or golimumab 100 mg at weeks 0, 4,8,12,16, and 20. Randomization was stratified by baseline MTX use (yes/no).…”
Section: Methodsmentioning
confidence: 99%
“…The Psoriatic Arthritis Response Criteria (PsARC) (12) and Disease Activity Score in 28 joints (DAS28) using the CRP level (DAS28-CRP) (13,14) were employed; dactylitis, enthesitis, and morning stiffness were also assessed. The presence and severity of dactylitis were scored on a scale of 0-3, where 0 ϭ no dactylitis and 3 ϭ severe dactylitis, in each digit of the hands and feet.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled trials of sulfasalazine, methotrexate, and gold have shown only marginal benefit compared with placebo in treating PsA (19,20,(25)(26)(27). Of these, only methotrexate had a marginal effect on the skin lesions of psoriasis (25).…”
Section: Discussionmentioning
confidence: 99%
“…Other end points included the ACR50 and ACR70 responses and the Psoriatic Arthritis Response Criteria (PsARC), a composite measure of patient's and physician's global assessments and tender and swollen joint scores (19). The effect of etanercept on psoriasis was measured as improvement in target lesions, in the dermatologist's static global assessment of psoriasis, and in the Psoriasis Area and Severity Index (PASI 50 and PASI 75) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Two other double-blind studies recently demonstrated the safety of SSZ in psoriatic arthritis and trends favoring SSZ for improved clinical outcome. The first study, performed in the United States, concerned 221 psoriatic arthritis patients treated with SSZ (2 &day) or placebo for 36 weeks (8). There were trends favoring SSZ for physician's overall assessment, patient's overall assessment, number of painful and swollen joints, and decreases in the ESR.…”
Section: To the Editormentioning
confidence: 99%